Factors that Affect Audit Delay - Sari, Yulan; Febyansyah, Andar (PT Inovasi Pratama Internasional, 2024)
The objective of this study was to ascertain whether there is a correlation between profitability, solvency, company size, company age, and audit opinion with audit delay. This study employs existing data on the financial statements of the mining sector, which have been adjusted to align with the sample criteria specified by the Indonesia Stock Exchange for the 2019-2023 research period. The data collection process employed a purposive sampling method, yielding a total of 70 data points from 14 mining companies over a five-year period. The research findings were subjected to a multiple linear regression analysis using the SPSS software. The results indicated that profitability exerts a negative influence on audit delay, whereas solvency and company size exert a positive influence on audit delay. Additionally, company age and audit opinion were found to have no effect on audit delay.